Effectiveness of oral health education methods on oral hygiene in children and adolescents with visual impairment: A systematic review. Issue 6 (6th May 2021) - Chua, Helene; Sardana, Divesh; Turner, Robin; Ting, Graeme; Ekambaram, Manikandan
Abstract: Background: Conventional methods of oral health education (OHE) are not suitable for children with visual impairment, as these methods usually involve visual demonstration with models or plaque‐disclosing dyes. Aim: To systematically review the literature to support the best approach for providing OHE to children and adolescents with visual impairment. Design: A systematic search of five electronic databases and grey literature was conducted. Randomized controlled trials that compared different OHE methods in children and adolescents with visual impairment were included. The Cochrane risk‐of‐bias tool (RoB 2) was used for the risk‐of‐bias assessment. The Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) framework was used to determine the certainty of evidence. Results: Nine randomized controlled trials with a total of 804 participants were included in this review. Seven OHE methods were compared. Seven studies were assessed to be at high risk of bias, one study was assessed to have some concerns, and one study was assessed to be at low risk of bias. The overall certainty of evidence was very low according to GRADE. Conclusion: There was insufficient evidence to recommend a particular method of OHE as more effective in improving the oral hygiene of children with visual impairment, but combination methods may show similar or better results.